OSMAC-Activated Alkaloid Diversity in a Mangrove Aspergillus sp. PLP1-F1 Drives Host-Directed Antibacterial Mechanisms - Fendi Setiawan; Wawan A Setiawan; Rudy T M Situmeang; Yuli Ambarwati; Ni Luh Gede Ratna Juliasih; Susianti Susianti; Peni Ahmadi; Masayoshi Arai; Andi Setiawan (Pandawa Institute, 2026)
The growing threat of multidrug-resistant (MDR) pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa necessitates discovery strategies that move beyond conventional single-target antibiotics. Here, we report a dereplication-guided pipeline applied to the mangrove-derived fungus Aspergillus sp. PLP1-F1, cultivated under an one strain–many compounds (OSMAC) solid-state fermentation using agro-industrial waste substrates to activate cryptic biosynthetic pathways. Molecular networking revealed 24 compounds with diverse chemical structures, including spiro-γ-dilactone, chinulin, anthraquinoline, notoamides, epi-fiscalins, okaramines, aspergillides, and cinatrins. The fungal extract exhibited potent antibacterial against resistant pathogen with a minimum inhibition concentration (MIC) of 250 µg/mL. To support these findings, pharmacokinetic profiling (ADME) identified 13 metabolites with favorable drug-likeness properties. Molecular docking against the bacterial division protein FtsZ highlighted three lead candidates epi-fiscalin C (16) (-8.89 kcal/mol), notoamide A (20) (-9.05 kcal/mol), and notoamide O (21) (-8.52 kcal/mol) with superior binding affinities compared to ciprofloxacin (-8.23 kcal/mol), suggesting interference with bacterial cytokinesis. Protein–protein interaction analyses further demonstrated that these alkaloids modulate host signaling networks, including EGFR–MAPK, PI3K–mTOR, caspase-mediated apoptosis, and matrix metalloproteinases. Functional enrichment additionally implicated IL‑17 signaling and neutrophil extracellular trap formation, pathways central to antibacterial immunity and inflammation control. Notably, FtsZ was not a central hub within the interaction networks, indicating that direct bacterial inhibition likely functions as a supportive mechanism alongside host-directed effects. Collectively this study underscores the value of OSMAC-driven metabolomics and systems pharmacology in accelerating natural product discovery, offering a scalable framework for identifying marine fungal metabolites with complex, resistance-resilient mechanisms of action.